Efficient Self‐Assembly of Di‐, Tri‐, Tetra‐, and Hexavalent Hosts with Predefined Geometries for the Investigation of Multivalency. Issue 37 (21st July 2015) - Linder, Igor; Leisering, Stefan; Puttreddy, Rakesh; Rades, Nadine; Rissanen, Kari; Schalley, Christoph A.
Abstract Coordination‐driven self‐assembly of differently shaped di‐ to hexavalent crown‐ether host molecules is described. A series of [21]crown‐7‐ and [24]crown‐8‐substituted bipyridine and terpyridine ligands was synthetized in a "toolbox" approach. Subsequent coordination to 3d transition metal and ruthenium(II) ions provides an easy and fast access to host assemblies with variable valency and pre‐defined orientations of the crown‐ether moieties. Preliminary isothermal calorimetry (ITC) titrations provided promising results, which indicated the host complexes under study to be suitable for the future investigation of multivalent and cooperative binding. The hosts described herein will also be suitable for the construction of various multiply threaded mechanically interlocked molecules.